RANCANG BANGUN SISTEM INFORMASI PERSEDIAAN BAHAN BAKU DAN ADMINISTRASI GUDANG MAJEMUK (STUDI KASUS KAROSERI PT. XYZ MALANG) - Denny Lukianto Kumala; Soetam Rizky Wicaksono (Jurnal Ilmiah Informatika, 2017)
In the manufacturing process Bus and Mini Bus, a lot of the raw materials required. Raw materials are stored at many warehouses (especially on Body PT. XYZ Malang). Materials / goods are highly vulnerable to lost or stolen. The most influential factor in it is the counting system inventory / materials and administration. These changes will have an impact on the process of goods more accurate calculation based on the demand of production. Losses will have a greater likelihood of being used if the system can not address the calculation of the goods/raw materials better.And administration system that can cope with the calculation of the goods/raw materials are better here is a system that can calculate expenditures for production based on the incoming bill alone, and can calculate the receipt of goods in accordance with the letter received by the supplier. The system can also provide reports based on existing transactions during a certain period.With the inventory system and the administration is then the difference between the goods that previously occurred can be minimized and raw material inventory accounting system can work better.